Societal lessons: narratives of Perak Tengah - fact or fiction? - Zakaria, Muhammad Salehuddin; Merman, Hairulnisak; Hashim Amir, Nur Muhammad Amin; Mazlan, Hilal (Faculty of Art and Design, 2025)
Fairy tales are folklores that readers are invited to imagine through an engaging storytelling method infused with moral values. In addition, folklores were once children's entertainment to strengthen friendships. The state of Perak Tengah is rich in historical stories; in addition to historical stories, there are several folklores found in the Central Perak area. This study aimed to identify and document folklore found in Central Perak as a reference source for future generations. The results of an interview with Mr. Mohammad Nazrin Bin Mohamad Suhaimi, who is a Lifetime Member of the Malaysian Historical Society (PSM) Perak State Branch. There are several folktales whose storylines are well-known and can serve as valuable life lessons. Among the stories of "Buluh Ape", "Pak Kaduk and Ikan Tapah", "Siam Menyerang Tanah Abang", "Padang Pak Beruk", "Gergasi Bota", and "Sang Kelembai" are stories that have been passed down from generation to generation by the people of Central Perak. Fairy tales like this should be used as guidelines and lessons for the current generation. In addition, each storyline is filled with moral values that can be applied in society.